2023
DOI: 10.1038/s41467-023-42970-4
|View full text |Cite
|
Sign up to set email alerts
|

Ocean warming drives rapid dynamic activation of marine-terminating glacier on the west Antarctic Peninsula

Benjamin J. Wallis,
Anna E. Hogg,
Michael P. Meredith
et al.

Abstract: Ice dynamic change is the primary cause of mass loss from the Antarctic Ice Sheet, thus it is important to understand the processes driving ice-ocean interactions and the timescale on which major change can occur. Here we use satellite observations to measure a rapid increase in speed and collapse of the ice shelf fronting Cadman Glacier in the absence of surface meltwater ponding. Between November 2018 and December 2019 ice speed increased by 94 ± 4% (1.47 ± 0.6 km/yr), ice discharge increased by 0.52 ± 0.21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 100 publications
1
3
0
Order By: Relevance
“…Although the glaciers on the AP are small compared to their neighbours in other parts of West Antarctica, they are changing rapidly such that AP contributed 14 % of Antarctica's total mass loss from 1992 to 2020 (Otosaka et al, 2023). Previous work has linked warming subsurface ocean waters to widespread glacier retreat along the west AP (Cook et al, 2016) and more recent work has further shown an ocean-driven ice tongue collapse and acceleration of Cadman Glacier on the west AP (Wallis et al, 2023a). The observations presented in this study develop this understanding by showing a widespread, quasisynchronous acceleration of grounding line discharge along the west AP linked to a period of high air and subsurface ocean temperatures.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Although the glaciers on the AP are small compared to their neighbours in other parts of West Antarctica, they are changing rapidly such that AP contributed 14 % of Antarctica's total mass loss from 1992 to 2020 (Otosaka et al, 2023). Previous work has linked warming subsurface ocean waters to widespread glacier retreat along the west AP (Cook et al, 2016) and more recent work has further shown an ocean-driven ice tongue collapse and acceleration of Cadman Glacier on the west AP (Wallis et al, 2023a). The observations presented in this study develop this understanding by showing a widespread, quasisynchronous acceleration of grounding line discharge along the west AP linked to a period of high air and subsurface ocean temperatures.…”
Section: Discussionsupporting
confidence: 70%
“…However, other 'low responders' do not always coincide with areas of shallow bathymetry and sometimes have responsive neighbouring glaciers. As in Wallis et al (2023a), these cases There is broad consistency in the timing of discharge trend changes amongst west AP glaciers (Figures 4 & 5). A vast majority of glaciers with significant discharge trend increases began to accelerate during the austral summer of 2020/2021 (Figure 5), though there is spread around this period (Figures 3 & 4d).…”
Section: Acceleration Of Grounding Line Dischargementioning
confidence: 54%
See 2 more Smart Citations